Respostas
respondido por:
3
(2y + 1)² = 8 + 2.(2y + 1)
4y² + 4y + 1 = 8 + 4y + 2
4y² + 4y + 1 = 4y + 10
4y² + 4y - 4y + 1 - 10 = 0
4y² - 9 = 0
4y² = 9
y² = 9/4
y = (+ ou -) √9/4
y = (+ ou - ) 3/2 S = { 3/2 , - 3/2 }
4y² + 4y + 1 = 8 + 4y + 2
4y² + 4y + 1 = 4y + 10
4y² + 4y - 4y + 1 - 10 = 0
4y² - 9 = 0
4y² = 9
y² = 9/4
y = (+ ou -) √9/4
y = (+ ou - ) 3/2 S = { 3/2 , - 3/2 }
respondido por:
1
◐(2y + 1)² = 8 + 2.(2y + 1)◐
4y² + 4y + 1 = 8 + 4y + 2
4y² + 4y + 1 = 4y + 10
4y² + 4y - 4y + 1 - 10 = 0
4y² - 9 = 0
4y² = 9
y² = 9/4
y =√9/4
y = 3/2 → S = { 3/2 , - 3/2 }←
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás